2015
DOI: 10.1364/oe.23.007779
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort stretched-pulse L-band laser using carbon-nanotube saturable absorber

Abstract: In the paper, a passively mode-locked erbium-doped fiber ring laser in the long-wavelength band (L-band) is presented by using a single-wall nanotube saturable absorber (SWNT-SA). The optical properties of the SWNT-SA are compared with those in the C-band in view of the absorbance spectrum and the power-dependent transmittance of the SWNT-SA film. The effects of the net cavity dispersion and the length of the erbium-doped fiber (EDF) on L-band stretched pulse generation are discussed. The designed stretched-pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…There are a few works that report the CNT-SA StP generation [77,127,135,136,139,[140][141][142][143][144][145][146][147][148][149], showing that Figure 4: CNT-SA mode-locked fiber laser covering the spectral region from near-infrared to mid-infrared: (A) typical schematic diagram of CNT-SA mode-locked fiber laser. Yao et al [123].…”
Section: Stretched Pulsementioning
confidence: 99%
“…There are a few works that report the CNT-SA StP generation [77,127,135,136,139,[140][141][142][143][144][145][146][147][148][149], showing that Figure 4: CNT-SA mode-locked fiber laser covering the spectral region from near-infrared to mid-infrared: (A) typical schematic diagram of CNT-SA mode-locked fiber laser. Yao et al [123].…”
Section: Stretched Pulsementioning
confidence: 99%
“…Compared with artificial SAs such as nonlinear polarization rotation (NPR) [1] and nonlinear optical loop mirror (NOLM) [2], real SAs have higher environmental persistence. For the sake of enhancing power resistance, these SAs have evolved from traditional semiconductor saturable absorber mirrors (SESAMs) [3] to one-dimensional and twodimensional materials, such as carbon nanotubes [4][5][6], graphene [7][8][9][10][11], black phosphorous [12][13][14][15], and transition-metal dichalcogenides (TMDs) [16][17][18][19][20]. Quite recently, it has been demonstrated that another novel material group of zero-dimension transition metal oxides (TMOs) including TiO 2 , ZnO, Al 2 O 3 and Fe 3 O 4 possesses efficient nonlinear SA properties [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Single-walled carbon nanotubes (SWCNTs) have extraordinary optical and electronic properties that make them attractive for numerous applications [1][2][3][4]. Recently, carbon nanotubes have been widely used as saturable absorbers (SAs) in pulsed fiber lasers owing to their large saturable absorption, ultrafast recovery time, and broadband operation [5][6][7][8][9][10]. To date, SWCNTbased SAs have been successfully used for mode-locking and Q-switching in fiber lasers, in which the operating wavelength ranges from 1.0 to 2.0 μm.…”
Section: Introductionmentioning
confidence: 99%